2022
DOI: 10.1101/2022.09.30.510341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What causes bird-building collision risk? Seasonal dynamics and weather drivers

Abstract: Bird-building collisions are a major source of wild bird mortality, with hundreds of millions of fatalities each year in the United States and Canada alone. Here, we use two decades of daily citizen-science monitoring to characterize day-to-day variation in building collisions and determine the factors that predict the highest risk times in two North American cities. We use these analyses to evaluate three potential causes of increased collision risk: heightened migration traffic during benign weather, increas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 48 publications
(98 reference statements)
1
4
0
Order By: Relevance
“…This difference stems from the presence of migrating juveniles in fall (Dokter et al., 2018) and the use of more easterly routes in fall compared to spring (La Sorte et al., 2014). As expected, and similar to studies in other cities in North America (Lao et al., 2022; Scott et al., 2023), we found that radar‐measured migration densities were generally higher in fall and that more collisions were recorded in NYC in fall than the spring.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This difference stems from the presence of migrating juveniles in fall (Dokter et al., 2018) and the use of more easterly routes in fall compared to spring (La Sorte et al., 2014). As expected, and similar to studies in other cities in North America (Lao et al., 2022; Scott et al., 2023), we found that radar‐measured migration densities were generally higher in fall and that more collisions were recorded in NYC in fall than the spring.…”
Section: Discussionsupporting
confidence: 91%
“…Collision monitoring efforts provide a unique opportunity to study a major source of mortality for birds during their annual cycles, and each new study fills a gap in our still imperfect knowledge about the true magnitude of birds killed in collisions with buildings. The effects of weather conditions (Lao et al., 2022; Lin et al., 2019; Panuccio et al., 2019; Scott et al., 2023) and nocturnal migration traffic (Elmore, Riding, et al., 2021) have been identified individually as factors in bird–building collisions. Our study provides evidence that these factors should be considered in tandem to predict bird collisions and to provide more nuanced guidance for the timing of collision mitigation programs such as Lights Out initiatives.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations